INTERPRETATION AS A STUDY OF ACADEMISSION IN THE WEST ORIENTALIST PERSPECTIVE - Rahman Hamid; Aviyah Asmaul Husna (LPPM UMC, 2024)
The interpretation of religious scriptures is object study scientific that has been There is since First, interpretation to all books holy expected capable fulfil current developments over time as well need public in operate rule applicable religious rules in religious scriptures. Quite a difference clear Can We feel on period quite contemporary significant like classification and methodology interpretation in understand book text holy religion. One of factor main is centrality of scripture That Alone as is done by three religions viz Judaism, Christianity and Islam in the century classical and medieval, both Bible , Bible and Al-Qur'an. Scripture text has long been recognized by the whole world, especially religious adherents of the century mid, fine as source authority important in society, guidelines life nor as the norm has been agreed . Deep method study This use referring research library to secondary and primary data, then processed and served use method descriptive analysis. Based on data that has been analyzed, then can concluded that there is group orientalist who is pro with the text of the Koran even Lots from those who explain interpretation classic even study interpretation classic with methodology in the west with objective prove originality scripture text. There are also later ones study linguistics of the Qur'an with apply rule Arab That Alone even discussion related Language neither do languages outside the Qur'an they leave. Because there are many scholar Muslim or scholar east the middle has a bad stigma to study orientalist .